TINDAK TUTUR DIREKTIF GURU DAN SISWA TAMAN KANAK-KANAK PERTIWI DALAM INTERAKSI BELAJAR MENGAJAR - Novita Carolina; Sudaryono Sudaryono (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
This study is aimed to describe the types and functions of directive speech act in teaching and learning activities at Pertiwi Kindergarten, Sumber Agung Village, Rimbo Ilir Subdistrict, Tebo Prefecture. This study uses qualitative approach, and descriptive as research design. Research instrument of this study is the researchers themselves as human instruments (planner, data collector, data interpreter, data analysts and data reporter). The research was taking place at Pertiwi Kindergarten, Sumber Agung Village, Rimbo Air Subdistrict, Tebo Prefecture. The data of this study is verbal data in the form of utterances which contain directive speech acts of teacher and students. Technique of collecting data which is used in this study is observation and field note. Meanwhile the data is analysed using pragmatic analysis. to test the validity of the research, the three steps is taken; the extension of observation, perseverance and triangulation. The result of teaching and learning interaction at Pertiwi Kindergarten showed that there are five types of speech acts performed by the teacher, they are ordering, pleading, demanding, advising, challenging. Meanwhile there are four functions of directive speech acts found, they are request, question, order and advice. Beside that, researchers found two types in the directive speech acts performed by the students, they are pleading and demanding. While there are two functions which are found, request and question.